Contractual Arrangements in Franchising: An Empirical Investigation - Agrawal, Deepak; Lal, Rajiv (Journal of Marketing Research, 1995)
The authors use primary data to empirically test several hypotheses about business format franchising on the basis of the theoretical model presented in Lal (1990). They find support for the hypothesis that royalty rate balances the incentives to the franchisor to invest in brand name with those to the franchisees to invest in retail service. Also consistent with the mixed strategy equilibrium, the authors find that royalty rate positively affects monitoring frequency, and that monitoring costs negatively affect service level. However, contrary to the theory, the authors find that monitoring costs inversely affect monitoring frequency among franchisors. They analytically extend Lal's model to incorporate heterogeneity in monitoring costs among franchisees belonging to the same franchisor and find strong empirical support for the hypothesis that monitoring costs inversely affect monitoring frequency within a franchise system.